Interventions to improve the experience of caring for people with severe mental illness: systematic review and meta-analysis. (April 2015) - Yesufu-Udechuku, Amina; Harrison, Bronwyn; Mayo-Wilson, Evan; Young, Norman; Woodhams, Peter; Shiers, David; Kuipers, Elizabeth; Kendall, Tim
Abstract : Background: Informal caregiving is an integral part of the care of people with severe mental illness, but the support needs of those providing such care are not often met. Aims: To determine whether interventions provided to people caring for those with severe mental illness improve the experience of caring and reduce caregiver burden. Method: We conducted a systematic review and meta-analyses of randomised controlled trials (RCTs) of interventions delivered by health and social care services to informal carers (i.e. family or friends who provide support to someone with severe mental illness). Results: Twenty-one RCTs with 1589 carers were included in the review. There was evidence suggesting that the carers' experience of care was improved at the end of the intervention by psychoeducation (standardised mean difference −1.03, 95% CI −1.69 to −0.36) and support groups (SMD =–1.16, 95% CI −1.96 to −0.36). Psychoeducation had a benefit on psychological distress more than 6 months later (SMD =–1.79, 95% CI −3.01 to −0.56) but not immediately post-intervention. Support interventions had a beneficial effect on psychological distress at the end of the intervention (SMD =–0.99, 95% CI −1.48 to −0.49) as did problem-solving bibliotherapy (SMD =–1.57, 95% CI −1.79 to −1.35); these effects were maintained at follow-up. The quality of the evidence was mainly low and very low. Evidence for combining these interventions and for self-help and self-management was inconclusive. Conclusions: Carer-focused interventions appear to improve the experience of caring and quality of life and reduce psychological distress of those caring for people with severe mental illness, and these benefits may be gained in first-episode psychosis. Interventions for carers should be considered as part of integrated services for people with severe mental health problems.